An electromyographic and kinematic study of the scapular stabilisers - Sonia Briel; Benita Olivier; Witness Mudzi (AOSIS, 2020)
Background: The scapular stabilisers, especially the actions of the force couples around the scapula, have an impact on the biomechanics of the scapula and the orientation of the glenoid. Objectives: The aim of our study was to determine both the muscle activity and the correlation between the muscle activity ratio of the lower force couple (the serratus anterior lower fibres and the lower trapezius). Methods: This was a quantitative cross-sectional study. Muscle activity of the dominant serratus anterior lower fibres and the lower trapezius muscles was collected with surface electromyographic (EMG) sensors and an inertial motion capture system was used to measure the three-dimensional (3D) shoulder flexion in the sagittal plane and abduction in the frontal plane. Graph Pad 5 (Prism, San Diego, CA, USA) was used for the statistical analysis. The confidence level was set at 95% (p 0.05). Results: Sixteen men and women participated in our study, with a mean (standard deviation) age of 25.4 (± 4.6) years, weight of 80.2 (± 25.1) kg and height of 171.6 (± 10.3) cm. A strong negative correlation was found at the start of the abduction (r = −0.623; p = 0.01) between the muscle activity of the serratus anterior lower fibres and the lower trapezius. Conclusions: The only significant increase in the mean EMG ratio of serratus anterior lower fibres versus the lower trapezius was present at 60% (from baseline) of abduction (p = 0.03). Clinical implications: The EMG activity ratio of serratus anterior lower fibres and lower trapezius remains variable in different movement planes.